2015
DOI: 10.5194/acpd-15-31133-2015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Global dimming and urbanization: did stronger negative SSR trends collocate with regions of population growth?

Abstract: Abstract. Global dimming refers to the decrease in surface solar radiation (SSR) observed from the 1960s to the 1980s at different measurement sites all around the world. It is under debate whether anthropogenic aerosols emitted from urban areas close to the measurement sites are mainly responsible for the dimming. In order to assess this urbanization impact on SSR, we use spatially explicit population density data of 0.08° resolution to construct population indices (PI) at 157 high data quality sites. Our stu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…This effect saturates when urbanization reaches certain level (ULE > 50%/UP > 20 million persons/PD > 250 person km −2 ), above which a further increase in urbanization won't generate a further alignment of urban and rural dimming, as well as a further strengthening of these trends. Similarly, Imamovic et al (2015) questioned the existence of an urbanization effect on surface solar radiation in the well urbanized regions of Europe and Japan but suggested that such an effect cannot be ruled out in Russia and China. It is assumable that the government interference with regulations on environmental pollution might start first in relatively urbanized/developed regions.…”
Section: Quantifying Urbanization Effects On Rural and Urban Sunshinementioning
confidence: 99%
See 2 more Smart Citations
“…This effect saturates when urbanization reaches certain level (ULE > 50%/UP > 20 million persons/PD > 250 person km −2 ), above which a further increase in urbanization won't generate a further alignment of urban and rural dimming, as well as a further strengthening of these trends. Similarly, Imamovic et al (2015) questioned the existence of an urbanization effect on surface solar radiation in the well urbanized regions of Europe and Japan but suggested that such an effect cannot be ruled out in Russia and China. It is assumable that the government interference with regulations on environmental pollution might start first in relatively urbanized/developed regions.…”
Section: Quantifying Urbanization Effects On Rural and Urban Sunshinementioning
confidence: 99%
“…To ensure that only urban and rural sites under similar climate conditions are compared, Wang et al (2014a) restricted the analysis to urban-rural station pairs within 2° × 2° areas and noted that the average urbanization effect on the mean and the trend of surface solar radiation over Europe, China, and Japan from 1961 to 1990 was small. Questioning the existence of an urbanization effect on surface solar radiation, Imamovic et al (2015) further examined the population indices (PI) at 157 worldwide sites for the 1960s-1980s and concluded that the urbanization effect based on PI is insignificant in Europe and Japan but cannot be ruled out in China and Russia. A similar conclusion was made in China by Wang et al (2012b) using diurnal temperature range (DTR) as a proxy for solar radiation, namely that urbanization effects exist not only during the global dimming period but also in the brightening period.…”
mentioning
confidence: 99%
See 1 more Smart Citation